Pemberitaan Crop Circle di Berbah, Yogyakarta: Kebergantungan Media pada Sumber Resmi - Mr Wendratama (Jurnal Komunikasi, 2010)
The media's heavy reliance on official sources means that government officials are sometimes able to control what journalists report and how they report it. In fact, many news reports are created or originated by officials, not by reporters. Most reporters get most of their stories quickly and efficiently from press conferences and the press releases that officials write, along with comments solicited from other officials. It is sometimes dangerous if media too relies on official sources and does not use alternative sources in their reporting since the tendency could lead to homogeneity of reporting and prevent audience from learning the thorough fact. In approaching a new phenomenon, more than any other 'normal' issues, media needs to do more research and investigative works in its coverage, and in depth reporting is the most visible way.